Co-solvent selection for supercritical fluid extraction of astaxanthin and other carotenoids from Penaeus monodon waste - Radzali, Shazana Azfar; Baharin, Badlishah Sham; Othman, Rashidi; Markom, Masturah; Abdul Rahman, Russly (Japan Oil Chemists' Society, 2014)
In recent years, astaxanthin is claimed to have a 10 times higher antioxidant activity than that of other carotenoids such as lutein, zeaxanthin, canthaxanthin, and β-carotene; the antioxidant activity of astaxanthin is 100 times higher than that of α-tocopherol. Penaeus monodon (tiger shrimp) is the largest commercially available shrimp species and its waste is a rich source of carotenoids such as astaxanthin and its esters. The efficient and environment-friendly recovery of astaxanthins was accomplished by using a supercritical fluid extraction (SFE) technique. The effects of different co-solvents and their concentrations on the yield and composition of the extract were investigated. The following co-solvents were studied prior to the optimization of the SFE technique: ethanol, water, methanol, 50% (v/v) ethanol in water, 50% (v/v) methanol in water, 70% (v/v) ethanol in water, and 70% (v/v) methanol in water. The ethanol extract produced the highest carotenoid yield (84.02 ± 0.8 μg/g) dry weight (DW) with 97.1% recovery. The ethanol extract also produced the highest amount of the extracted astaxanthin complex (58.03 ± 0.1 μg/g DW) and the free astaxanthin content (12.25 ± 0.9 μg/g DW) in the extract. Lutein and β-carotene were the other carotenoids identified. Therefore, ethanol was chosen for further optimization studies.